Original sin? revising the revisionist critique of the 1963 Operation Coldstore in Singapore - Ramakrishna, Kumar (Institute of Southeast Asian Studies, 2015)
"Revisionist" or "alternative" historians have increasingly questioned elements of the Singapore Story - the master narrative of the nation's political and socioeconomic development since its founding by the British in 1819. Much criticism focuses especially on one defining episode of the Story: the internal security dragnet mounted on 2 February 1963 against Communist United Front elements on the island, known to posterity as Operation Coldstore. The revisionists claim that Coldstore was mounted for political rather than security reasons and actually destroyed a legitimate Progressive Left opposition - personalized by the charismatic figure of Lim Chin Siong - rather than a dangerous Communist network as the conventional wisdom holds. Relying on both declassified and some previously unseen classified sources, this book challenges revisionist claims, reiterating the historic importance of Coldstore in helping pave the way for Singapore's remarkable journey from Third World status to First in a single generation.